Sclerosing Angiomatoid Nodular Transformation of the Spleen (SANT): CT and MR Imaging Features of Five Cases with Pathological Correlation - Jialin Yuan; Jingshan Gong (International Journal of Radiology and Radiation Oncology - Peertechz Publications, 2016)
Objective: To  describe  imaging  features  of  sclerosing  angiomatoid  nodular  transformation  (SANT)  with pathologic correlation. Methods: Imaging findings of five cases of SANT were retrospectively analyzed and compared with pathological manifestations. Results:All the five cases of SANT were solitary and round masses with maximum diameter ranged from  cm  to  9  cm.  In  ultrasound,  all  the  lesions  were  well  circumscribed  with  one  of  hypoecho  and  four  of  hyperecho  with  posterior  enhancement.  Two  masses  were  of  hypoattenuation  and  one  was  of  isoattenuation at pre-contrast CT scanning. At MRI, the two masses appeared isointensity on T1 weighted images, and hypointense nodules with diffuse signal void spots on T2 weighted images. After intravenous contrast materials, all the five masses showed peripheral circle enhancement at the hepatic arterial phase.The enhanced circle persisted and radial enhanced lines occured in three masses and progressive filling in 2 masses at the portal vein phase. At the delay phase, progressive enhancement resulted in two isodensity masses and one hypoattenuation mass with radial enhanced lines at CT, and one obvious hyperintensity mass with central hypointensty scar and one spoke -like appearance enhancement at MR images.The progressive enhancement and hypointensity at T2 weighted MR images were coresponded to abundent fibrous stroma at pathological examinations, while the signal void might result from hemosiderin in the angiomatoid nodules. Conclusions:CT and MRI can demonstrate some characteristic findings of SANT, which can facilitate radiologists to make correct diagnosis.